Дослідження та застосування комбінаторних конфігурацій для інноваційних пристроїв і технологій - Riznyk, Volodymyr (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2023)
This paper is devoted to the memory of Solomon Wolf Golomb (1932–2016) — a famous American mathematician, engineer, and professor of electrical engineering. He was interested in developing techniques for improving the quality indices of engineering devices and systems with respect to performance reliability, transmission speed, positioning precision, and resolving ability based on novel combinatorial configurations. In 1996 S. Golomb have supported the project “Researches and Applications of the Combinatorial Configurations for Innovative Devices and Process Engineering” as a scientific collaboration with the Former Soviet Union (FSU) research team from Lviv Polytechnic State University (Ukraine) under the Cooperative Grant Program by CRDF (U.S.). The underlying project to be edited by S. Golomb is presented, and short information on the development of the researches and applications of optimized systems with ring structure given.